Characterization of 1600 Hamamatsu 16-anode photomultipliers for the MINOS Far detector - Lang, K; Day, J; Ellerts, S; Fuqua, S; Guillen, A; Kordosky, M; Lang, M; Liu, J; Opaska, W; Proga, M; Vahle, P; Winbow, A; et al. (2005)
We are reporting results of the characterization of over 1600 multi-anode R5900-00-M16 photomultipliers manufactured by Hamamatsu Photonics K.K., and installed in the MINOS Far detector. We have conducted extensive tests of the uniformity of gain and collection efficiency of individual anodes, the cross-talk among all 16 channels, the dark noise, and the linearity of response. In our studies we used a blue light-emitting diode to illuminate phototubes through 1.2 mm diameter optical fibers. In this paper, we present summaries of the main characteristics of the tested photomultipliers. © 2005 Elsevier B.V. All rights reserved.